2011
DOI: 10.2527/jas.2010-2942
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feed withdrawal and dietary energy source on muscle glycolytic potential and blood acid-base responses to handling in slaughter-weight pigs1

Abstract: The effects of dietary energy source and feed withdrawal on muscle glycolytic potential (GP) and blood acid-base responses to handling were investigated in slaughter-weight pigs (initial BW 94.7 ± 1.01 kg). Crossbred pigs (n = 96; 48 barrows, 48 gilts) were used in a randomized complete block design with a 4 × 2 × 2 factorial arrangement of treatments: l) diet [control, high fat (10% supplemental fat), low-digestible carbohydrate (20% total starch), and high-fat/low-digestible carbohydrate (10% supplemental fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
(33 reference statements)
0
6
0
1
Order By: Relevance
“…The reduction of ADFI in the present study may be attributed to the poor palatability [ 1 ] and early satiety [ 17 ] induced by the high fibre diet. Similarly, Bertol et al, [ 18 ] also reported that pigs fed high fibre diets had less feed intake compared with those fed corn and soybean-based diets. Although the higher soybean oil in diet can improve feed efficiency [ 19 ] and decrease heat increment [ 20 ], in this study, diet C did not prevent the reduction of ADG, nor was it beneficial to FCR.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The reduction of ADFI in the present study may be attributed to the poor palatability [ 1 ] and early satiety [ 17 ] induced by the high fibre diet. Similarly, Bertol et al, [ 18 ] also reported that pigs fed high fibre diets had less feed intake compared with those fed corn and soybean-based diets. Although the higher soybean oil in diet can improve feed efficiency [ 19 ] and decrease heat increment [ 20 ], in this study, diet C did not prevent the reduction of ADG, nor was it beneficial to FCR.…”
Section: Discussionmentioning
confidence: 97%
“…These data were contrary to the results of Rosenvold et al, [ 1 ], who reported that pigs fed diets with lower level of digestible carbohydrate (compared with a standard diet) reduced muscle glycogen contents. Additionally, the insulin resistance induced by high fat feeding can reduce glucose uptake and glycogen synthesis in muscle [ 18 ]. Thus, the muscle glycogen content should not be unchanged by the low starch high fat diet in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in live weight between AWIRS and CON pigs (Table 2) also may be a source of variation in the easiness to handle between these pigs. Bertol et al (2011) also reported that heavier pigs needed more handler interventions during handling than lighter pigs.…”
Section: Animal Behaviormentioning
confidence: 95%
“…Current guidelines do not recommend ramps steeper than 20°t o be used for fixed ramps (Warriss et al, 1991) or than 25°for adjustable ramps. However, as market pigs have become heavier and difficult to move (Bertol et al, 2005(Bertol et al, , 2011Rocha et al, 2016), recent works recommend the maximum ramp slope to be reduced to 15° (Grandin, 2012;Faucitano and Goumon, 2018).…”
Section: Slippingmentioning
confidence: 99%